Enhancing Capacities of Digital Extension and Advisory Services in Odisha, India - Dominic, Ditty Maria; Mitta, Nimisha; Sulaiman V, Rasheed; Bharti, Preeti; Sharma, Sheetal (2022)
While several digital platforms and applications developed for farmers collect data and information, more is needed to know about their use by the Extension and Advisory Services (EAS) to provide more relevant advice or design a data-informed extension. This report discusses what needs to be done to enhance the capacities of EAS based on in-depth reviews of farmers' use of three digital farmer services available in Odisha and interactions with select stakeholders who are familiar with and are part of these services. We found that EAS stakeholders needed to be fully aware of the types of data and information available or how best they could be used. We identified that four specific types of capacities need to be strengthened coherently and systematically.